Mediasi employer branding pada pengaruh employee’s perceived job terhadap employee engagement - Widyana, Suci Fika; Rezza, Ali Mohamad; Anggraeni, Angga Dewi; Oscar, Bheben (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The digitalization of the economy is forcing companies to shift their business landscape towards digital. The company is expected to improve organizational performance and reclaim their marketshare from competitor. The purpose of this study was to analyze the increase in employee engagement through employee perceived work through employer branding mediation at one delivery service company X in Bandung. The subjects of this study were employees of the shipping service company X, the sampling technique used simple random sampling with a total of 150 employees. Data analysis was performed using PLS-SEM. The diprecision of the research results will show that the perception of employees' work has a significant effect on employer branding and employee engagement. Another finding is that Employer Branding can be the perfect mediator for increasing Employee Engagement through Employee's Perceived Job. This means that if a company wants to increase Employee Engagement, it needs to make efforts to improve Employer Branding and Employee Perceived Job.